2020
DOI: 10.14687/jhs.v17i2.6005
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 immune system and exercise

Abstract: COVID-19, which became a current issue as a result of the pneumonia cases with unknown etiology in Wuhan City, Hubei Province of China on December 31, 2019, has started to spread throughout the world and deaths related to it have increased rapidly. Isolation, which is an important step in the control of this disease, has many physiological and psychological effects. Initiating a sudden quarantine situation means a radical change in the lifestyle of the population. Changing lifestyles and behaviours may result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…[23] According to the results of the studies, intense and competitive exercise is not suitable in these conditions and can reduce the body's immune response and lead to a higher risk of infection with coronavirus. [26,27] Most studies have emphasized avoiding long term sitting and sedentary lifestyle, which is very common, especially in young people, by wasting too much time on social media and networks. [26,28] In addition to improving the function and capacity of the immune system, physical activity can help reduce anxiety and stress, improve mood, control many underlying diseases such as diabetes, hypertension, cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…[23] According to the results of the studies, intense and competitive exercise is not suitable in these conditions and can reduce the body's immune response and lead to a higher risk of infection with coronavirus. [26,27] Most studies have emphasized avoiding long term sitting and sedentary lifestyle, which is very common, especially in young people, by wasting too much time on social media and networks. [26,28] In addition to improving the function and capacity of the immune system, physical activity can help reduce anxiety and stress, improve mood, control many underlying diseases such as diabetes, hypertension, cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, as another side of the same coin, the sudden onset of a quarantine period not only implies a rapid change in people's lifestyles but also can impact the health of these isolated persons, since it favours impairment in dietary habits, 4 changes in psychosocial behaviour 5 and reduced levels of physical activity in all age individuals. 6 In this regard, it is noteworthy to emphasize that one of the most impacted habits in the current quarantine were those associated with regular physical exercise (rPE), including indoor or outdoor practice. [7][8][9] Corroborating these pieces of information, recent studies demonstrated that during COVID-19 confinement, the overwhelming majority of the population declared not only a significant reduction of daily self-reported physical activity as well as an increase in sedentary time.…”
Section: Brief Summary Of the Covid-19 Era And Its Impact On The LImentioning
confidence: 99%
“…34 Systemic elevations of myokines, particularly of interleukin-6 (IL-6), not only can optimize lipid and glucose metabolism but can also exert indirect antiinflammatory effects by promoting the secretion of classical anti-inflammatory cytokines, IL-1ra and IL-10, with concurrent inhibition of TNF-α action. 6 This is one of the most important myokines-driving anti-/ pro-inflammatory regulation mechanisms recently illustrated by several authors as the yin-yang relationship. 35 However, we cannot exclude the key role of the redox signals hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO) in adjusting the extension of oxidative stress and the inflammation processes following any type of exercise.…”
Section: Introductionmentioning
confidence: 98%
“…The Covid-19 pandemic has had many physiological and psychological effects on individuals [ 13 ]. The rapid launch of the quarantine implementation caused a radical change in the lifestyle of the population [ 14 ]. Mass social isolation can result in problems with mental health in most people [ 12 ].…”
Section: Introductionmentioning
confidence: 99%